Bacterial Hepatitis Caused by Staphylococcus pseudintermedius Associated with Hepatic Copper Accumulation in a Dog: A Case Report - Nadalin, Amanda Regina; Marucci Thomaz, Bruno (Brazilian Journal of Case Reports, 2026)
Hepatopathies in dogs often present diagnostic challenges due to the overlap of infectious, metabolic, and inflammatory etiologies. This report describes a case of bacterial hepatitis caused by Staphylococcus pseudintermedius associated with hepatic copper accumulation in a dog, emphasizing the diagnostic approach, clinical progression, and therapeutic management. A female dog was presented with nonspecific clinical signs and biochemical evidence of hepatocellular injury. Serial hematological and biochemical analyses revealed progressive liver enzyme alterations, prompting further diagnostic investigation. Definitive diagnosis was established through liver biopsy, histopathological evaluation, bacterial culture with antimicrobial susceptibility testing, and hepatic copper quantification. Histopathology demonstrated inflammatory changes consistent with bacterial hepatitis, along with cholestasis and hepatocellular degeneration. Microbiological culture identified Staphylococcus pseudintermedius as the causative agent. Hepatic copper concentration was markedly increased, exceeding reference limits. Targeted antimicrobial therapy and supportive hepatic treatment were initiated, resulting in progressive clinical improvement and gradual normalization of laboratory parameters during follow-up. The temporal response to therapy suggests that bacterial hepatitis was the primary condition, with secondary copper accumulation likely associated with cholestasis. However, limitations in the assessment of copper distribution prevent definitive differentiation between primary and secondary hepatopathy. This case highlights the importance of comprehensive diagnostic evaluation in canine hepatopathies and underscores the potential coexistence of infectious and metabolic factors in liver disease. Recognition of such multifactorial conditions is essential for accurate diagnosis and appropriate therapeutic decision-making in small animal practice.